Material properties on enamel and fissure of surface pre-reacted glass-ionomer filler-containing dental sealant. Issue 2 (August 2018) - Hirayama, Koji; Hanada, Takashi; Hino, Ryoko; Saito, Kan; Kobayashi, Mayu; Arakaki, Makiko; Chiba, Yuta; Nakamura, Norihiko; Sakurai, Takeshi; Iwamoto, Tsutomu; Fukumoto, Satoshi; Yamada, Aya
Abstract: Purpose: In pediatric dentistry, sealants have been used to prevent caries. Due to its material properties such as fluoride-releasing ability and physical strength, surface pre-reacted glass (S-PRG) filler is added primarily to resin-based dental materials for clinical use. In this study, we investigated the properties of S-PRG filler containing sealant. Methods: Before using sealant, the primer was applied to extracted bovine incisors. Scanning electron microscopy (SEM) observation revealed that the primer treatment caused no structural changes of enamel surface, unlike conventional phosphoric acid etching. Further, shear bond strength test was performed to measure the initial strength and durability after thermal cycling. Bond strength of S-PRG filler containing sealant was comparable to those of other sealants even though the former does not involve phosphoric acid etching. In addition, after treating the enamel surface with the primer or phosphoric acid, it showed excellent flowability in the primer group compared to phosphoric acid treatment. Results: SEM observation showed that the sealant sealed the enamel surface as it migrated to reach the deep areas of the fissures. When the marginal sealing ability of the sealant was evaluated based on dye penetration, no dye penetration in the marginal region was observed in any specimens. In addition, measurement of the pH of an acid solution containing a cured specimen of the sealant containing S-PRG filler showed that the solution's pH became more alkaline as the immersion time increased. Conclusion: These findings suggest that the sealant is an extremely effective material for preventing caries.